2022
DOI: 10.1002/nml.21513
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the nonprofit accountability‐charitable donations relationship through the publicness lens

Abstract: This study integrates the publicness theory and the benefits theory of nonprofit finance to examine how nonprofits' financial and non-financial accountability criteria relate to the private charitable contributions they receive. The analysis of the National Center for Charitable Statistics' IRS Statistics of Income Sample Files 2008-2012 and Nonprofit IRS E-filers 2010-2017 reveals that the relationships between accountability criteria and private donations vary significantly depending on the nonprofits' fundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Charitable contributions : The literature suggests that receiving an external accreditation of transparency leads to increased donations by alleviating the information asymmetry between the organization and the donors (Mitchell, 2018). Therefore, external accreditations of transparency and accountability may be considered more important in a donative organization while there is less of an incentive for an organization generating more income from commercial activities to invest in receiving external accreditations of transparency (Hoang & Lee, 2022). The regression model includes the percentage of charitable contributions in total revenue.…”
Section: Methodsmentioning
confidence: 99%
“…Charitable contributions : The literature suggests that receiving an external accreditation of transparency leads to increased donations by alleviating the information asymmetry between the organization and the donors (Mitchell, 2018). Therefore, external accreditations of transparency and accountability may be considered more important in a donative organization while there is less of an incentive for an organization generating more income from commercial activities to invest in receiving external accreditations of transparency (Hoang & Lee, 2022). The regression model includes the percentage of charitable contributions in total revenue.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research shows that donations are influenced by the financing and operational characteristics of nonprofits. For example, nonprofits with lower administrative overhead, executive or other staff compensation, and fundraising costs are generally viewed as better stewards of their financial resources and are expected to attract more donative revenue (Charles & Kim, 2016; Calabrese, 2011; Galle and Walker, 2014; Hoang & Lee, 2022; Rossi et al, 2022). The effect of executive compensation on donations is typically negative, with multiple studies finding that higher compensation reduces future donative returns (Galle and Walker, 2014, 2016; Yan & Sloan, 2016).…”
Section: Financing and Operational Factors Influencing Nonprofit Dona...mentioning
confidence: 99%
“…Some studies have identified significant relationships between donation levels and specific governance indicators such as external audits (Kitching, 2009) and board composition (Callen et al, 2003). Other studies have observed effects of a comprehensive measure of governance consisting of various governance-related components (Boland et al, 2020;Harris et al, 2015;Hoang & Lee, 2022;Newton, 2015). Although the compositions of governance measures differ across studies, a large body of evidence supports a positive association between governance measures and donation levels.…”
Section: Hypothesesmentioning
confidence: 99%